CIRCULATION OF INFLUENZA VIRUSES AMONG HUMANS AND SWINE IN THE REGIONS OF NORTHERN AND WESTERN KAZAKHSTAN IN 2017–2018 - S. B. Baiseiit; N. S. Ongarbayeva; M. K. Kalkozhayeva; M. G. Shamenova; N. T. Saktaganov; G. V. Lukmanova; N. G. Klivleyeva (Инфекция и иммунитет, 2018)
.